2009
DOI: 10.1002/app.29993
|View full text |Cite
|
Sign up to set email alerts
|

Study of PET/PP/TiO2 microfibrillar‐structured composites, part 1: Preparation, morphology, and dynamic mechanical analysis of fibrillized blends

Abstract: The objective of this study was to manufacture and investigate a novel microfibrillar-reinforced material based on fibrillized blends of polyethyleneterephthalate (PET), polypropylene (PP), and TiO 2 nanoparticles (300 nm and 15 nm in size). The uncompatibilized and compatibilized blends (polypropylene grafted maleic anhydride as compatibilizer) were extruded and subsequently cold-drawn into strands with a draw ratio of 10. The effects of compatibilizer and TiO 2 particles on the structure and properties of dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
0
24
0
1
Order By: Relevance
“…In the literature, the effect of adding TiO 2 on the morphology of a PET/PP blend (rich in PP) has been studied . As reported by Li et al ., in the case of the PET/PP binary blends the particles locate in the PET droplets . For TiO 2 nanoparticles treated with polyalcohol, Li et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the effect of adding TiO 2 on the morphology of a PET/PP blend (rich in PP) has been studied . As reported by Li et al ., in the case of the PET/PP binary blends the particles locate in the PET droplets . For TiO 2 nanoparticles treated with polyalcohol, Li et al .…”
Section: Resultsmentioning
confidence: 99%
“…The authors state that particles tend to migrate from PP phase to PET phase, which is more thermodynamically favored for TiO 2 . Regarding the rheological properties, the results corresponding to the viscosity ratio of the different polymer phases has been studied to explain the morphological changes analyzing the effect of the presence of TiO 2 in the viscosity of PP or PET . Notwithstanding these interesting outcomes, there is still a considerable lack of knowledge on other relevant physicochemical properties, such as thermal properties, linear rheology, rheology under shear flow, and transport properties of PET/polyolefins containing TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al concluded that a substantial increase in the elasticity of nanosilica‐filled PSF matrix would facilitate the formation of LCP fibrils in polysulfone (PSF)/liquid crystalline polymers (LCP) blends. Li et al found that the preferential location of TiO 2 particles shifted from the PET dispersed phase to the PP matrix in compatibilized PET/PP blends and then resulted in a reduction of the viscosity ratio facilitating the deformability of the dispersed PET droplets after drawing . Li prepared in situ carbon black/PET microfibers in CB/PET/PE composties, as the CB content increased to a critical point, which greatly increased the viscosity ratio between the PET minor phase and PP matrix, the well‐defined CB/PET microfibers could not be formed .…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that a polymer blend presents the possibility to improve mechanical properties because of synergistic effect . Furthermore, properties of a polymer blend can be further enhanced by adding nanofillers such as organoclay, titanium dioxide, and carbon black . Carbon nanotube (CNT) is also a good candidate for polymer nanocomposites because of their excellent mechanical and electrical properties with a large aspect ratio .…”
Section: Introductionmentioning
confidence: 99%